2009
DOI: 10.1021/nl802818d
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Highly-Ordered TiO2 Nanotube Arrays and Their Use in Dye-Sensitized Solar Cells

Abstract: Highly ordered TiO(2) nanotubes were successfully fabricated using a nanoporous alumina templating method. A modified sol-gel route was used to infiltrate the alumina pores with Ti(OC(3)H(7))(4) which was subsequently converted into TiO(2) nanotubes. The average external diameter, tube lengths, and wall thickness achieved were 295 nm, 6-15 microm, and 21-42 nm, respectively. Diffraction data reveals that the nanotubes consist solely of the anatase phase. Dye-sensitized solar cells using TiO(2) nanotube arrays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
204
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(204 citation statements)
references
References 31 publications
0
204
0
Order By: Relevance
“…242 It is believed that TiO 2 nanotubes could be superior to nanorods or nanowires because of the availability of inner as well as outer walls of tubes for dye adsorption. [225][226][227][228][229][230][231][232][233][234][235][236][237][238][239][240][241][242][243][244] In 2007, Zhu et al reported the dynamics of electron transport and recombination in DSSCs incorporating oriented TiO 2 nanotube (NT) arrays. 229 The NT arrays consisted of closely packed NTs, several microns in length, with typical wall thickness and inter-tube spacing of 8-10 nm and pore diameters of about 30 nm, as shown in Fig.…”
Section: Selected Recent Progressmentioning
confidence: 99%
“…242 It is believed that TiO 2 nanotubes could be superior to nanorods or nanowires because of the availability of inner as well as outer walls of tubes for dye adsorption. [225][226][227][228][229][230][231][232][233][234][235][236][237][238][239][240][241][242][243][244] In 2007, Zhu et al reported the dynamics of electron transport and recombination in DSSCs incorporating oriented TiO 2 nanotube (NT) arrays. 229 The NT arrays consisted of closely packed NTs, several microns in length, with typical wall thickness and inter-tube spacing of 8-10 nm and pore diameters of about 30 nm, as shown in Fig.…”
Section: Selected Recent Progressmentioning
confidence: 99%
“…In principle, any of these materials can be subjected to a variety of chemical reactions under a suitable atmosphere to fabricate nanostructures from a virtually inexhaustible list of material compositions. The fabricated nanostructures can find applications in plasmonics 21 , plasmonic nanolithography 22 , photon detection 23 , nanophotonics 24 , memristors 25 and metallic nanostructures 26 for nanoelectronics, control of cell behaviour through patterned surfaces 27 and in low-cost fabrication of highly ordered TiO 2 structures, which have been shown to significantly increase the efficiency of dye-sensitized solar cells 28 .…”
mentioning
confidence: 99%
“…The alumina template is then removed by immersing the samples in 6 M NaOH solution. Kang (Kang et al, 2009) fabricated highly ordered TiO 2 nanotubes using such nanoporous alumina template method. Such nanotubes with 15 μm lengths were heat treated at 500 °C for 30 min and soaked in N3 dye for 24 h. DSC based on the nanotubes showed a conversion efficiency of as high as 3.5% and a maximum IPCE of 20% at 520 nm.…”
Section: Tio 2 Nanotubesmentioning
confidence: 99%